Freeze-Thaw Performance and Moisture-Induced Damage Resistance of Base Course Stabilized with Slow Setting Bitumen Emulsion-Portland Cement Additives - Mojtaba Shojaei Baghini; Amiruddin Ismail (Advances in Materials Science and Engineering)
Freeze-thaw (FT) cycles and moisture susceptibility are important factors influencing the geotechnical characteristics of soil-aggregates. Given the lack of published information on the behavior of cement-bitumen emulsion-treated base (CBETB) under environmental conditions, especially freezing and thawing, this study investigated the effects of these additives on the CBETB performance. The primary goal was to evaluate the resistance of CBETB to moisture damage by performing FT, Marshall conditioning, and AASHTO T-283 tests and to evaluate the long-term stripping susceptibility of CBETB while also predicting the liquid antistripping additives to assess the mixture’s durability and workability. Specimens were stabilized with Portland cement (0%–6%), bitumen emulsion (0%–5%), and Portland cement-bitumen emulsion mixtures and cured for 7 days, and their short- and long-term performances were studied. Evaluation results of both the Marshall stability ratio and the tensile strength ratio show that the additions of additives increase the resistance of the mixtures to moisture damage. Results of durability tests performed for determining the resistance of compacted specimens to repeated FT cycles indicate that the specimen with the 4% cement-3% bitumen emulsion mixture significantly improves water absorption, volume changes, and weight losses. This indicates the effectiveness of this additive as a road base stabilizer with excellent engineering properties for cold regions.